Using acoustic emission to assess the tensile behaviour of textile reinforced cementitious (TRC) matrix composites. (6th December 2021) - Reboul, N.; Saidi, M.; Gabor, A.
Abstract: The tensile behaviour of textile reinforced cementitious matrix composites (TRC) is investigated using acoustic emission monitoring. Three carbon-TRC-composites with different reinforcement ratios are tested. An unsupervised pattern recognition technique is used to classify the signals. In combination with tests on TRC-components, these clusters of signals are correlated with matrix cracking, textile–matrix interface damage, shear frictional mechanisms and textile tensile behaviour. The contribution of each mechanism during loading is quantified. Finally, the acoustic data are compared qualitatively with the evolutions of crack width (measured by Digital Image Correlation) and load-transfer length (obtained by Distributed Fibre Optic Sensing measurement). A model to predict crack width from load-transfer length is proposed and gives satisfactory results. This paper shows that the local behaviour of TRC is reflected in acoustic activity and that AE offers valuable information about damage processes in TRC-composites. Highlights: TRC-composites under tensile loading were monitored by acoustic emission. AE signals were separated into clusters, then associated with damage mechanisms. Load-transfer lengths showing interface damage were estimated from acoustic data. A model for predicting crack widths from load-transfer lengths is proposed.